Eksplorasi Kampung Kramat sebagai daerah cagar budaya - Muflihah, Sayyidatul (Maliki Interdisciplinary Journal, 2023)
Kampung Kramat is a cultural heritage area that holds significant value in terms of history, aesthetics, science, and ethnology. It is located within the Kasin Public Cemetery area. The purpose of this research is to determine the origin of Kampung Kramat, the correlation between the graves and Kampung Kramat, as well as the community life in Kampung Kramat. The research method employed is qualitative-descriptive research, which includes documentation, observation, and interviews. The research findings indicate that Kampung Kramat needs to be preserved and continuously maintained as it can become a unique cultural heritage site.